Screening of starch degrader from soil - Praventhran, Janardanan (2006)
Starch as we know is the main source of carbohydrate. Since carbohydrate is always somehow linked to industry, we need to produce enzyme that can degrade carbohydrate. Presently the enzyme used is amylase but lately many are venturing into other enzymes especially the ones extracted from bacteria. My research here is concentrating on a specific enzyme named cyclomaltodextrin glycosyltransferase or CGTase. Firstly the bacteria are carefully screened from the sample soil collected from a local corn field. Then after the bacteria have been identified it will be analyzed for its characteristics and the crude enzyme will be tested on its effect by changes of temperature, pH, and carbon and nitrogen source. From this research I have managed to screen a typical strain of CGTase producing bacteria where after running tests such as gram staining, spore staining, and acid fast the type and characteristics of the bacteria was known.